Shelf Life Study of Cocoa Vinegar Using Accelerated Shelf Life Testing (ASLT) Method Based on Arrhenius Approach - Putra, G.P. Ganda; Wartini, Ni Made (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 1 (2018): Scientific Journal of Food Technology, 2018)
Liquid pulp by-product of fermentation of cocoa beans can be processed into cocoa vinegar.  Cocoa vinegar as a new food product needs to be determined its shelf life. The objectives of this study were: (1) to know the stability of cacao vinegar distillate products during storage, and (2) to determine the shelf life of cocoa vinegar distillate using Accelerated Shelf-Life Testing (ASLT) method based on Arrhenius approach for determination of expired  period of product. In this study, the storage of cocoa vinegar distillate for 10 weeks at three different temperatures, namely: 28oC, 40oC, and 50oC, and each experiment was done twice repeated. Weekly observations were done on the characteristic parameter of cocoa vinegar distillate. The results obtained show that: (1) during storage there is a decrease in acetic acid concentration, but an increase in pH, TSS and clarity value (OD600) of cocoa vinegar distillate; (2) the determination of shelf life is based on pH characteristics with equation of Ln k = -2217.2 (1/T) + 5.1875, which shelf life at temperatures: 10oC, 20oC, 28oC, 40oC, and 50oC respectively: 35.28 weeks (8.23 months), 27.01 weeks (6.30 months), 22.09 weeks (5.15 months), 16.65 weeks (3.89 months), and 13.37 weeks (3.12 months). The data of shelf life may be used to specify the expiration period, which must be included in the packaging label.